The Nexus between the Exportation of Social Sustainability Certifications that Restrict Malaysian Palm Oil Companies and their Profitability: A Panel on Driscoll and Kraay Standard Errors and a Fully Modified Ordinary Least Square Approach - Haseeb, Muhammad; Hye, Qazi Muhammad Adnan (International Journal of Management and Sustainability, 2020)
Currently, due to the restriction of social sustainability certifications, exports of biofuel to Europe and other countries are a crucial phenomenon that financially affect companies. The primary aim of the current study is to investigate the effects on the profitability of palm oil export companies in Malaysia that have social sustainability certifications. Data were extracted from the annual reports of companies that export biofuel and have had social sustainability certifications between 2009 to 2018. The results indicate that exports have a positive financial effect on palm oil export companies in Malaysia. These findings present guidelines to policymakers on removing restrictions on exports and developing policies that enhance the exportation of biofuel, thereby enhancing the economic growth of the country.